2024
DOI: 10.3390/microorganisms12030485
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Mutations and Conservation of InlA in Listeria monocytogenes

Lingling Li,
Yan Wang,
Ji Pu
et al.

Abstract: Listeria monocytogenes (L. monocytogenes) is a pathogen that is transmitted through contaminated food and causes the illness known as listeriosis. The virulence factor InlA plays a crucial role in the invasion of L. monocytogenes into the human intestinal epithelium. In addition, InlA enhances the pathogenicity of host strains, and different strains of L. monocytogenes contain varying variations of InlA. Our study analyzed a total of 4393 published L. monocytogenes genomes from 511 sequence types (STs) of dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Internalin proteins can affect L. monocytogenes biofilm formation, as well as adhesion, virulence, internalization into eukaryotic cells, and survival in the environment [53,54]. The inlA gene is a major virulence factor of L. monocytogenes, and truncations due to premature stop codons (PMSCs) caused virulence attenuation [55], while it led to significantly enhanced biofilm formation [31]. It has been found that lineage II strains carried inlA PMSC mutations more frequently than lineage I strains [56].…”
Section: Discussionmentioning
confidence: 99%
“…Internalin proteins can affect L. monocytogenes biofilm formation, as well as adhesion, virulence, internalization into eukaryotic cells, and survival in the environment [53,54]. The inlA gene is a major virulence factor of L. monocytogenes, and truncations due to premature stop codons (PMSCs) caused virulence attenuation [55], while it led to significantly enhanced biofilm formation [31]. It has been found that lineage II strains carried inlA PMSC mutations more frequently than lineage I strains [56].…”
Section: Discussionmentioning
confidence: 99%